2020
DOI: 10.1063/5.0033107
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond protein dynamics in a red/green cyanobacteriochrome revealed by transient IR spectroscopy

Abstract: Over the last decades, photoreceptive proteins were extensively studied with biophysical methods to gain a fundamental understanding of their working mechanisms and further guide the development of optogenetic tools. Time-resolved infrared (IR) spectroscopy is one of the key methods to access their functional non-equilibrium processes with high temporal resolution but has the major drawback that experimental data are usually highly complex. Linking the spectral response to specific molecular events is a major … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 61 publications
(87 reference statements)
1
48
0
Order By: Relevance
“…This result is in good agreement with a previous resonance Raman study of the related CBCR Slr-g3, where it was shown that the Trp sub-states are not sensed by other vibrational modes associated with ring D, but strongly by ring A. 16 The published FTIR spectra of other red/green CBCRs differ quite substantially for C O A , where the other proteins only show a weak bleach band in the FTIR difference spectra, 25,35–37 and only AmI-g2 displays the sharp positive feature. In line with the assignment of the two C O A bands in the Pr state, we conclude that in the Pg state of AmI-g2, the C O A must be located in a hydrophobic environment that does not allow H-bonding.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is in good agreement with a previous resonance Raman study of the related CBCR Slr-g3, where it was shown that the Trp sub-states are not sensed by other vibrational modes associated with ring D, but strongly by ring A. 16 The published FTIR spectra of other red/green CBCRs differ quite substantially for C O A , where the other proteins only show a weak bleach band in the FTIR difference spectra, 25,35–37 and only AmI-g2 displays the sharp positive feature. In line with the assignment of the two C O A bands in the Pr state, we conclude that in the Pg state of AmI-g2, the C O A must be located in a hydrophobic environment that does not allow H-bonding.…”
Section: Discussionsupporting
confidence: 91%
“…In the difference-FTIR spectra, this broadening in a heterogeneous environment is reflected by a sharp negative contribution at 1674 cm −1 on top of a broad positive background, which was also observed at similar frequencies in the difference FTIR spectra of AnpixJg2, 35,36 NpR6012g4 37 and Slr1393g3. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the GSB bands are less distorted in the BV-bound variant, and the approximations hold better compared to PCB. Φ L further depends on the excitation wavelength, but in case of the closely related red/green CBCR Slr-g3, similar GSB ratios were observed independent of Q-band 26 or Soret-band excitation, 20 which is an indication that this factor plays only a minor role in red/green CBCRs. The values for Φ L were calculated from the fit at the Lumi GSB minima.…”
Section: Estimation Of Quantum Yieldsmentioning
confidence: 69%
“…Samples were illuminated with red and far-red laser diodes to prepare the Pg state in the case of PCB-adduct (HL6750MG, Thorlabs), and the Po state in case of the BV-adduct (HL7302MG) in a sample reservoir. Electronically synchronised fs-lasers were used for the generation of the pump and probe pulses 19 as described earlier 20 with only minor adaptations in the pump light for the present study. Here, compressed pulses with 8 ps duration and with a power of 0.5 µJ at 385 nm were used for excitation of all samples.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%